A chance constraint approach to peak mitigation in electric vehicle charging stations. (September 2021) - Casini, Marco; Vicino, Antonio; Zanvettor, Giovanni Gino
Abstract: The increased penetration of plug-in electric vehicles asks for efficient algorithms to be adopted in parking lots equipped with charging units. In this paper, the peak power minimization problem for a plug-in charging station is addressed. A chance constraint approach is adopted in order to minimize the daily peak power, allowing for a tolerance on the charging service customer satisfaction expressing the probability that a vehicle leaves the station violating the agreed level of charge. Numerical simulations are provided to evaluate the performance of the proposed approach as well as to make a comparison with other techniques.